The case against psychiatric drugs - Whitaker, Robert (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2016)
The conventional narrative in psychiatry tells of a psychopharmacological revolution that began with the arrival of chlorpromazine in asylum medicine in 1955. Today, psychiatric drugs are understood to be safe and effective treatments for a variety of disorders. However, a close review of the scientific literature, stretching over a span of 50 years, reveals a paradox: medications that are effective over the short term may increase the chronicity of a disorder over the long-term. A case study of antipsychotics best illustrates this paradox. The small number of researchers investigating this paradox are focusing on drug-induced “oppositional tolerance” as an explanation for the poor long-term outcomes of medicated patients.